A Comprehensive Case Study on the Successful Treatment of Perianal Fistula in a Four-Year-Old Male - Abdulqadir, Aliaa A.; RAJU, MADANU DAVID PAUL; Patel , Mukul H (Journal of Contemporary Medical Sciences, 2023)
This case study gives a thorough account of how a four-year-old boy who had been experiencing recurrent discomfort and perianal discharge for six months was diagnosed, treated, and then recovered. An MRI fistulogram revealed a transphincteric fistula with both the internal and exterior apertures placed at the 9 o'clock position, despite the absence of concomitant diseases and prior procedures. The treatment method used methylene blue infiltration to verify the internal aperture and then metal probe probing of the track. From the exterior to the internal opening, a partial fistulotomy was carried out, and the raw proximal track was treated with Kshara sutra. Surprisingly, the fistula was fully cured in just three months. This case study gives priceless information that could direct future treatments and serves as a testimonial to the efficiency of such a therapy method in controlling juvenile fistulas.